2016
DOI: 10.1353/hsj.2016.0011
|View full text |Cite
|
Sign up to set email alerts
|

The Intersectionality of Border Pedagogy and Latino/a Youth: Enacting Border Pedagogy in Multiple Spaces

Abstract: In this one-year qualitative study, the authors examined how border pedagogy is enacted by two Latino/a high school teachers in a border community in Southern California. Through classroom observations, the authors documented powerful student discussions that named complex borders (Giroux, 1992) that existed in their daily lives. We drew from conocimientos (understandings) (Anzaldúa, 1987), conscientizacíon (critical consciousness) (Freire, 1970), and cariño (authentic care) (Valenzuela, 1999) as theoretical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Humanizing aspects of border pedagogies are also demonstrated by Stewart & Gachago (2016) in a transcontinental border crossing digital storytelling project which results show that through the project notions of otherness were critically demystified, which allows students to counter global hegemonic discourses. In current research activism is also seen as an essential part of border pedagogy (Ramirez, Ross, & Jimenez-Silva, 2016). In their qualitative study on two U.S. Latina teachers in a border community in California Ramirez, Ross and Jimenez-Silva (2016) found that the teachers applied border pedagogy through authentic care/cariño (Valenzuela, 1999), critical consciousness/ concientizacíon (Freire, 1970), and community activism (Ramirez, Ross, & Jimenez-Silva, 2016, p. 318).…”
Section: Literature Reviewmentioning
confidence: 90%
See 3 more Smart Citations
“…Humanizing aspects of border pedagogies are also demonstrated by Stewart & Gachago (2016) in a transcontinental border crossing digital storytelling project which results show that through the project notions of otherness were critically demystified, which allows students to counter global hegemonic discourses. In current research activism is also seen as an essential part of border pedagogy (Ramirez, Ross, & Jimenez-Silva, 2016). In their qualitative study on two U.S. Latina teachers in a border community in California Ramirez, Ross and Jimenez-Silva (2016) found that the teachers applied border pedagogy through authentic care/cariño (Valenzuela, 1999), critical consciousness/ concientizacíon (Freire, 1970), and community activism (Ramirez, Ross, & Jimenez-Silva, 2016, p. 318).…”
Section: Literature Reviewmentioning
confidence: 90%
“…In current research activism is also seen as an essential part of border pedagogy (Ramirez, Ross, & Jimenez-Silva, 2016). In their qualitative study on two U.S. Latina teachers in a border community in California Ramirez, Ross and Jimenez-Silva (2016) found that the teachers applied border pedagogy through authentic care/cariño (Valenzuela, 1999), critical consciousness/ concientizacíon (Freire, 1970), and community activism (Ramirez, Ross, & Jimenez-Silva, 2016, p. 318). Ramirez, Ross and Jimenez-Silva (2016) in their theoretical framework for their study draw on nepantla (Anzaldúa, 1987) as a place where the transformation of identities can take place.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…Sensoy also found that students' own positionings along lines of race, class, or gender were not predictive of the narratives they created. This study, like many others (e.g., Howard, 2004;Ramirez et al, 2016) focused more on students' counternarratives of their experiences with racism or sexism than on their ability to identify the structural nature of these phenomena or their relationship to meritocracy.…”
Section: Impacts Of Critical Pedagogy On Understandings Of Social Inequalitymentioning
confidence: 99%